LEXICAL FEATURES OF SOMATISMS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article is dedicated to the study of the lexical features of somatisms. The research deeply analyzes the formation of words, word combinations, and phrases related to body parts, as well as their linguistic characteristics. Furthermore, relevant examples are provided to reveal the semantic flexibility, metaphorical richness, and cultural specificity of somatisms. The article highlights the importance of somatisms in understanding language and culture, emphasizing their role in cognitive and linguistic research.